2020
DOI: 10.1029/2019je006292
|View full text |Cite
|
Sign up to set email alerts
|

The Range of Jupiter's Flow Structures That Fit the Juno Asymmetric Gravity Measurements

Abstract: The asymmetric gravity field measured by the Juno spacecraft has allowed the estimation of the depth of Jupiter's zonal jets, showing that the winds extend approximately 3,000 km beneath the cloud level. This estimate was based on an analysis using a combination of all measured odd gravity harmonics, J3, J5, J7, and J9, but the wind profile's dependence on each of them separately has yet to be investigated. Furthermore, these calculations assumed the meridional profile of the cloud‐level wind extends to depth.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
30
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 43 publications
(116 reference statements)
9
30
0
Order By: Relevance
“…S7), suggesting that if alternative jets exists in the mid-latitudes, their amplitude should be around ±40 m s −1 . These results are consistent with Duer et al (2020) replaced with random jets there (Fig. 1b).…”
Section: Variants Of the Flow Structuresupporting
confidence: 88%
“…S7), suggesting that if alternative jets exists in the mid-latitudes, their amplitude should be around ±40 m s −1 . These results are consistent with Duer et al (2020) replaced with random jets there (Fig. 1b).…”
Section: Variants Of the Flow Structuresupporting
confidence: 88%
“…This had been previously noted by Ingersoll et al (2017) based solely on the PJ1 (August 2016) observations, but they had suggested that the relationship between temperate brightness gradients and the zonal jets was rather poor. Using these same PJ1 data, Duer et al (2020) also showed the correlation between winds and MWR brightness observations. Using data from subsequent perijoves, filtering via the deconvolution process of Oyafuso et al (2020), and by taking the gradient ∆, we have shown that the correlation with the cloud-top winds is actually much better than originally thought.…”
Section: Discussionmentioning
confidence: 78%
“…It is natural to ask whether the inferred winds are consistent with the results of Juno's gravity measurements (Kaspi et al, 2018;Guillot et al, 2018), which suggest a variety of potential wind profiles decaying to the 3000-km level, depending on the sensitivity to the measured odd gravity harmonics J 3 , J 5 , J 7 and J 9 (Duer et al, 2020).…”
Section: Comparison To Juno Gravitymentioning
confidence: 72%
See 2 more Smart Citations